New cases of splenic artery aneurysms. Multiple aneurysms - Praderi, José; Gateño, Nisso; Estefan, Alberto; Cassinasco, Angeles; Praderi, Raúl (Cirugía del Uruguay, 1987)
5 new cases of splenic artery aneurysms treated In Uruguay are presentad. Our natlonal casulstlc Is 19 ca• ses. lmportance of laparoscopy and abdominal dlagnostic puncture in case of intraperitonaal rupture Is polnted out.